Evaluation of anti-Fel d 1 IgY ingredient for pet food on growth performance in kittens - Hedrick, Erik D.; Matulka, Ray A.; Conboy-Schmidt, Lisa; May, Kimberly A. (Frontiers in Veterinary Science, 2024)
The domestic cat (Felis catus) is one of the most common pets. Worldwide, approximately 1 in 5 adults are sensitive to cat allergens. The major cat allergen is the secretoglobulin Fel d 1, which is primarily produced in the salivary and sebaceous glands. Chickens produce IgY antibodies, which are similar in structure to mammalian IgG. When chickens are exposed to Fel d 1, anti-Fel d 1-specific IgY (AFD1) is produced and is naturally concentrated in egg yolk. The aim of this study was to evaluate the tolerability, effects on growth and food consumption, and potential adverse effects of a chicken egg product ingredient containing AFD1 in kittens. The feeding groups included Group 0 (0 ppm AFD1), Group 1 (8 ppm AFD1), and Group 2 (16 ppm AFD1). Throughout the study, there were no signs of nutritional deficiency or adverse clinical events in any of the subjects. Administration of a chicken egg product ingredient containing AFD1 in the diet (whether in coating or combination of coating and top dress) had no significant effect on body weight nor food consumption, and all subjects maintained a healthy Body Condition Score (BCS) throughout the study. Moreover, there were no biologically significant differences in the mean clinical chemistry and hematology parameters. This study demonstrated that a diet formulated to contain up to 16 ppm AFD1, included in the coating and the top-dress of dry kitten food, was well tolerated, promoted adequate growth, and exhibited no adverse effects.